The Anastasia Syndrome, and Other Stories - Clark, Mary Higgins (New York A Pocket Books, 1991)
A woman's nagging sense of deja vu leads her to discover the truth behind a series of terrorist bombings in the title story, in a collection of short fiction by a leading suspense writer.
Keywords: Novel